Protein Kinase C Beta in the Tumor Microenvironment Promotes Mammary Tumorigenesis - Wallace, Julie A.; Pitarresi, Jason R.; Sharma, Nandini; Palettas, Marilly; Cuitiño, Maria C.; Sizemore, Steven T.; Yu, Lianbo; Sanderlin, Allen; Rosol, Thomas J.; Mehta, Kamal D.; Sizemore, Gina M.; Ostrowski, Michael C. (Frontiers in Oncology, 2014)
Protein kinase C beta (PKCβ) expression in breast cancer is associated with a more aggressive tumor phenotype, yet the mechanism for how PKCβ is pro-tumorigenic in this disease is still unclear. Interestingly, while it is known that PKCβ mediates angiogenesis, immunity, fibroblast function and adipogenesis, all components of the mammary tumor microenvironment (TME), no study to date has investigated whether stromal PKCβ is functionally relevant in breast cancer. Herein, we evaluate mouse mammary tumor virus–polyoma middle T-antigen (MMTV–PyMT) induced mammary tumorigenesis in the presence and absence of PKCβ. We utilize two model systems: one where PKCβ is deleted in both the epithelial and stromal compartments to test the global requirement for PKCβ on tumor formation, and second, where PKCβ is deleted only in the stromal compartment to test its role in the TME. MMTV–PyMT mice globally lacking PKCβ live longer and develop smaller tumors with decreased proliferation and decreased macrophage infiltration. Similarly, when PKCβ is null exclusively in the stroma, PyMT-driven B6 cells form smaller tumors with diminished collagen deposition. These experiments reveal for the first time a tumor promoting role for stromal PKCβ in MMTV–PyMT tumorigenesis. In corroboration with these results, PKCβ mRNA (Prkcb) is increased in fibroblasts isolated from MMTV–PyMT tumors. These data were confirmed in a breast cancer patient cohort. Combined these data suggest the continued investigation of PKCβ in the mammary TME is necessary to elucidate how to effectively target this signaling pathway in breast cancer.